Why are Latin American countries in the limbo of open-access scientific publications? - Chavarría Vargas, Max (2024)
Open Access (OA) model in scientific journals has brought about a range of benefits in terms of information accessibility. However, the high costs associated with Article Processing Charges (APCs) have posed a significant challenge for many scientists, leaving them in a ‘limbo’, where their ability to publish in reputable journals is contingent upon their financial capacity. Here, we intend to highlight the challenges faced by Latin American scientists that have arisen as a direct consequence of the implementation of the OA, specifically: (i) difficulties in disseminating our scientific work due to the impossibility of covering the high APCs imposed by journals, and (ii) the strong emergence and consolidation in our region of publishers with predatory practices. We urge the scientific community to establish policies that contribute to equity in OA models and to defend the right of Latin American scientists not only to read science freely but also to be read.